Impact of Islamic values on the leadership style of Muslim women academics in Malaysia - Hamzah, Siti Raba'ah; Hamzah, Azimi; Othman, Jamilah; Sharmila Devi, (SAGE Publications, 2016)
The Problem: The religious background of Muslim women academic leaders in Malaysia guides them in performing demanding roles in managing multiple responsibilities. To date, little is known about the impact of Islamic values on Muslim women leaders in institutions of higher learning, even though Islam is the official religion in Malaysia. In addition, the field of human resource development has done little to explore the leadership style of Muslim women. The Solution: This paper presents findings and recommendations of a research conducted for the purpose of exploring, understanding, and presenting the impact of Islamic values on the leadership style of Muslim women academics in Malaysia. This inquiry is significant because it’s open the new sight for HRD scholar and practitioners to explore HRD in a leadership, women leadership, religious, and the role of Muslim faith in women academic leaders. It is hoped that the findings of this research will encourage HRD scholars and practitioners to consider integrated dimension to their scholarly thought and practice related to leadership style. The Stakeholders: The outcomes of this research will be of interest to those women who are currently in leadership roles in academia, as well as those women interested in moving into these roles. It should also be of interest to higher education administrators and, particularly, those within higher education charged with developing leaders. Human resource development scholars and practitioners will also benefit from the contributions of this article to our general understanding of women in leadership roles.